2009
DOI: 10.1016/j.ijpe.2008.08.025
|View full text |Cite
|
Sign up to set email alerts
|

The Q(s,S) control policy for the joint replenishment problem extended to the case of correlation among item-demands

Abstract: We develop an algorithm to compute an optimal Q(s,S) policy for the joint replenishment problem when demands follow a compound correlated Poisson process. It is a non-trivial generalization of the work by Nielsen and Larsen (2005). We make some numerical analyses on two-item problems where we compare the optimal Q(s,S) policy to the optimal uncoordinated (s,S) policies. The results indicate that the more negative the correlation the less advantageous it is to coordinate. Therefore, in some cases the degree of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Though the Q(s, S) policy also sends out an order when the cumulative demand reaches Q, it only replenishes an item if its inventory position is less than, or equal to, its reorder point. Nielsen and Larsen (2005) and Larsen (2009) work out an analytical solution procedure for the Q(s, S) policy. Mustafa Tanrikulu, Ş en, and Alp (2010) relax the Q(s, S) policy through dropping S. They propose the (s, Q) policy, by which an order with size Q is triggered whenever any item's inventory position falls to its reorder point.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the Q(s, S) policy also sends out an order when the cumulative demand reaches Q, it only replenishes an item if its inventory position is less than, or equal to, its reorder point. Nielsen and Larsen (2005) and Larsen (2009) work out an analytical solution procedure for the Q(s, S) policy. Mustafa Tanrikulu, Ş en, and Alp (2010) relax the Q(s, S) policy through dropping S. They propose the (s, Q) policy, by which an order with size Q is triggered whenever any item's inventory position falls to its reorder point.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is not hard to show stochastically increasing and linear continuous time demand mentioned by Rao (2003), such as compound Poisson or Brownian motion with drift, could be discretized to discrete time demand. Some recent papers consider demand correlations among different items, for instance, Larsen (2009) and Feng, Wu, Muthuraman, and Deshpande (2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this case, the demand was considered as a compound Poisson distribution for each type of product to be replenished in the same order. In addition, decomposition methods were also present, in which the JRP was decomposed in several single-item problems one for each type of product, as in Huang & Chen (2007), Kayiş et al (2008), andLarsen (2009), and the solution comprehended the merge of each sub-solution obtained. Huang & Chen (2007) 1 , Eynan & Kropp (2007) 1 , Moon et al (2008) 1,2 , Yao (2010) 1 , Narayanan & Robinson (2010) 2 , Roushdy et al (2011) 1 , Karalli & Flowers (2011) …”
Section: Stochastic Demandmentioning
confidence: 99%
“…In the stochastic review period they found (s, S) policy for a fixed order size Q, and the solution of sub-problems could be obtained by a heuristic algorithm [14]. Larsen proposed algorithms to solve the JRP based on optimal Q(s, S) policy when the demands of items followed a compound correlated Poisson process [15]. Mustafa Tanrikulu et al proposed a new optimal replenishment policy; namely, (s, Q) policy.…”
Section: Review Of Previous Literaturementioning
confidence: 99%